Can transparency undermine peer review? A simulation model of scientist behavior under open peer review. (2nd June 2022) - Bianchi, Federico; Squazzoni, Flaminio
Abstract: Transparency and accountability are keywords in corporate business, politics, and science. As part of the open science movement, many journals have started to adopt forms of open peer review beyond the closed (single- or double-blind) standard model. However, there is contrasting evidence on the impact of these innovations on the quality of peer review. Furthermore, their long-term consequences on scientists' cooperation and competition are difficult to assess empirically. This paper aims to fill this gap by presenting an agent-based model that simulates competition and status dynamics between scholars in an artificial academic system. The results would suggest that if referees are sensitive to competition and status, the transparency achieved by open peer review could backfire on the quality of the process. Although only abstract and hypothetical, our findings suggest the importance of multidimensional values of peer review and the anonymity and confidentiality of the process.